An exploratory review of temperament research: Trends and implications for theory and intervention in the fields of developmental psychology and education - Farbach, Karline Rose (My University, 2008)
Temperament research has grown exponentially over the past decades. Diverse though the body of temperament research may be, due to the interest of many fields of study in this construct, fairly considerable areas of consensus in the understanding of temperament as a psychological construct has been achieved over the years. In other words, there is general agreement in the field that the notion that temperament is biological and genetic and that temperament plays a role in developmental contexts. A review of recent temperament research (from 1998 to 2005) was done for this study. An automated search of many databases was conducted, as well as a hand search of well-accredited journals, mostly from the disciplines of developmental psychology and education. Based on selected criteria, 102 studies were chosen for review. The findings of this study, based on an analysis of the selected studies, follow. For example, it was found that the large majority of the studies selected were methodologically sound. It was also noted that the various themes elicited from the analysis tended to follow the trends temperament research was following before 1998, at the beginning of this review. Evidence was also found that suggested there was a shift from using psychomedical frameworks towards constructivist, ecosystemic frameworks for underpinning temperament research, which suggests that contemporary temperament research is more likely to be studied from a developmental stance than it was a few years ago. The findings from this analysis were applied to issues in temperament research and practice in the context of developmental psychology and education.
Keywords: temperament; psychology; development; literature review; education